PENGARUH KEPEMILIKAN INSTITUSIONAL, KEPEMILIKAN MANAJERIAL, DAN KOMPENSASI RUGI FISKAL TERHADAP PENGHINDARAN PAJAK - Rananda Septanta (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
This study aims to obtain empirical evidence about the effect of institutional ownership, managerial ownership, and fiscal loss compensation on tax avoidance, in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2021. This type of research is quantitative and the method used is panel data analysis with the help of the Eviews 9 program, to obtain a comprehensive picture of the relationship between one variable and another. This research was conducted on manufacturing companies listed on the Indonesia Stock Exchange. By using purposive sampling according to the specified criteria. The amount of data collected is 101 financial statement data. The results of this study indicate that institutional ownership and managerial ownership have no effect on tax avoidance while fiscal loss compensation has an effect on tax avoidance, overall three variables have a simultaneous effect on tax avoidance Regency.